TANGGUNG JAWAB KANTOR PELAYANAN DAN KEKAYAAN NEGARA (KPKNL) ATAS OBJEK JAMINAN FIKTIF YANG DILELANG (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 696/PK/PDT/2012) - IRA YULIA ALFIANI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Suhandi, SH, MH2. Dr. Sutiarnoto, SH, MHum3. Dr. Jelly Leviza, SH, MHum There are pros and cons in its process. One of them is an auction winner cannot have the object he has bought through the foreclosure sale since the object of the auction done by KPKNL is fictive. The research used juridical prescriptive analytic method. Secondary data were obtained from primary, secondary, and tertiary legal materials. The data were gathered by conducting library research, documentary study, and interviews and analyzed qualitatively. The conclusion is that the fulfillment of the principles of auction on a fictive auctioned collateral for an auction winner, viewed from the perspective of the principles of auction, is not implemented properly. Nowadays, auction is only regulated repressively in its legal protection, but it is not regulated preventively in legal protection for an auction winner in the case of fictive auctioned collateral. The liability of KPKNL for a fictive auctioned object is only administrative.Keywords: KPKNL, Fictive Collateral